Long-Term Temporal Trends of Nosema spp. Infection Prevalence in Northeast Germany: Continuous Spread of Nosema ceranae, an Emerging Pathogen of Honey Bees (Apis mellifera), but No General Replacement of Nosema apis - Gisder, Sebastian; Schüler, Vivian; Horchler, Lennart L.; Groth, Detlef; Genersch, Elke (Frontiers in Cellular and Infection Microbiology, 2017)
The Western honey bee (Apis mellifera) is widely used as commercial pollinator in worldwide agriculture and, therefore, plays an important role in global food security. Among the parasites and pathogens threatening health and survival of honey bees are two species of microsporidia, Nosema apis and Nosema ceranae. N. ceranae is considered an emerging pathogen of the Western honey bee. Reports on the spread of N. ceranae suggested that this presumably highly virulent species is replacing its more benign congener N. apis in the global A. mellifera population. We here present a 12 year longitudinal cohort study on the prevalence of N. apis and N. ceranae in Northeast Germany. Between 2005 and 2016, a cohort of about 230 honey bee colonies originating from 23 apiaries was sampled twice a year (spring and autumn) resulting in a total of 5600 bee samples which were subjected to microscopic and molecular analysis for determining the presence of infections with N. apis or/and N. ceranae. Throughout the entire study period, both N. apis- and N. ceranae-infections could be diagnosed within the cohort. Logistic regression analysis of the prevalence data demonstrated a significant increase of N. ceranae-infections over the last 12 years, both in autumn (reflecting the development during the summer) and in spring (reflecting the development over winter) samples. Cell culture experiments confirmed that N. ceranae has a higher proliferative potential than N. apis at 27°C and 33°C potentially explaining the increase in N. ceranae prevalence during summer. In autumn, characterized by generally low infection prevalence, this increase was accompanied by a significant decrease in N. apis-infection prevalence. In contrast, in spring, the season with a higher prevalence of infection, no significant decrease of N. apis infections despite a significant increase in N. ceranae infections could be observed. Therefore, our data do not support a general advantage of N. ceranae over N. apis and an overall replacement of N. apis by N. ceranae in the studied honey bee population.